The role of L-carnitine in distance athletes - Grivas, G. V. (International Journal of Sports Science, 2018)
The purpose of this study was to perform a systematic review and summarize the current literature regarding L-carnitine and the potential role of sports especially in distance athletes. L-carnitine is a naturally occurring compound that plays an important role in mitochondrial ß-oxidation. The main role of L-carnitine is to promote weight loss by increasing calorie expenditure. Also, L-carnitine plays an important role on recovery from strenuous exercise and may help to achieve quicker recovery and reduce muscle soreness. Finally, the results indicate that there is uncertainty in regards to how L-carnitine helps athletic performance. There are only three studies in the literature showing beneficial effects of L-carnitine on performance of athletes. On the contrary, three other studies have shown no effect of L-carnitine on performance.